O Plano Diretor de Curitiba (Lei n° 14.771/2015) e sua relação com a função social da propriedade na perspectiva dos direitos urbanísticos e ambiental - Pinheiro, Adilson Ivan Caropreso (2016)
The city of Curitiba has been regarded as a forefront synonymous of urban development and ecological balance. However, as in most large Brazilian cities, Curitiba faces social problems, especially in the area of urban property and its own environmental preservation facing urban invasions motivated by that. However, the Federal Constitution guaranteed the municipal administrators an essential element for the management of their cities, the Master Plan. This instrument, the Master Plan, which was regulated by the City Statute, provided a strategic planning for the municipality, in its development and a greater democratic management of its own citizens interests, the townspeople. This Master's dissertation aims to analyze the legal force of Curitiba’s Master Plan 2015 (Law No. 14,771 / 2015) in the treatment given by its creators (Society, Municipal Administration and Municipal Legislature) to the social function of property. It was elected as a paradigm for analysis of this work the Urban Law and Environmental Law and their determinations that guide the use, exploitation of urban land and the preservation of the natural and urban environment within the legal orders generated by the approval of the project law update of the master plan of the city of Curitiba. Through research in academic databases, in specific literature and in national jurisprudence, parameters were established for ranking the effectiveness of the orders contained in the full master plan of Curitiba (immediately applicable) contained (only part can be applied) and limited (it needs a future regulation to be effective). The results obtained throughout this work are posted at the end of this paper and they express that from the 96 articles directly related to the urban law area, environmental law and the property contained in the new law of Curitiba’s Master Plan, 40% of them have limited effectiveness, 16% of the articles have contained efficiency and 44% have their full effect, that is, 56% of the articles focused on the theme’s work does not have full applicability of their policies, which imposes thinking to the external observer that the law responsible for the urban development of the city for the next 10 years, at this moment, does not have sufficient efficacy to transform the nebulous aspect of the fair and correct distribution of property and its social function in the municipality of Curitiba.